Female Empowerment and the Politics of Language: Evidence Using Gender-Neutral Amendments to Subnational Constitutions. Issue 4 (17th October 2021) - Newman, Benjamin J.; DeMora, Stephanie L.; Reny, Tyler T.
Abstract: This letter explores language politics as it concerns gender, and investigates the adoption of amendments that introduce gender-neutral language to subnational constitutions via popular initiative. Embracing theories of female empowerment based on resource acquisition and shrinking gender differentials in economic resources, the authors argue that popular support for these initiatives will be higher in contexts where female and male incomes are closer to parity. The study tests this expectation using city-level historical administrative data in California on Proposition 11 in 1974 – the first American state to hold a popular vote on amending its constitution to include only gender-neutral language. It finds that greater parity in income between women and men is associated with greater voter support for the initiative. This result holds after controlling for conceivable confounders, fails to emerge when analyzing gender-irrelevant ballot measures, and replicates when analyzing similar measures held in three jurisdictions in other states.